Hand book in Portuguese now available - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1988)
A book that has proved very useful to field workers since its translation into English has now been translated into Portuguese. Handbook for field trials in Technical Cooperation was first written in German and published by GTZ. Its translation into...